Lost to follow-up: a challenge over 10 years. Issue 12 (2nd December 2021) - Poliseno, Mariacristina; Bavaro, Davide Fiore; Di Gennaro, Francesco; De Vita, Giuseppina; Girardi, Enrico; Saracino, Annalisa; Monno, Laura; Angarano, Gioacchino; Lo Caputo, Sergio
ABSTRACT: The loss of patients to follow up is a major issue related to HIV management. Our research was aimed to evaluate, in a single Italian centre, the rate of patients lost to follow-up (LFU) over 10 years, to describe their socio-demographic and clinical features, and to identify predictors of disengagement from care. Between 2008 and 2017, 563 subjects were LFU. Over the years, the proportion of LFU on the number of patients followed per year, decreased from 6.5% in 2008 to 4.8% in 2017 ( p for trend   =   0.255 ). Four different subgroups were identified among LFU:116 patients resulted untraceable; 192 had died; 144 were re-engaged elsewhere; 111 were subsequently re-engaged in our centre. Old age (OR 1.08, 95%, CI = 1.06–1.11; p   <   0.001 ), AIDS (OR = 1.66, 95% CI = 1.04–2.64; p = 0.031 ), drug addiction (OR = 1.91, 95% CI = 1.07–3.41; p  =  0.027 ) were predictors of death at multivariable analysis. Main predictors of being untraceable were non-Italian nationality (OR = 4.23, 95% CI = 2.19–8.16; p   <   0.001 ) and a short history of cART (OR = 0.93, 95% CI = 0.88–0.99; p  =  0.026 ). Subjects living far from our Centre were often re-engaged elsewhere (OR = 2.36, 95% CI = 1.34–4.15; p  =  0.002 ). According to our analysis, the problem LFU is still relevant: strategies to empower retention in care are thus necessary.